The Failure of Global Capitalism : From Cape Breton to Colombia andBeyond. - Gibbs, Terry (Cape Breton University Press, 2017)
The Failure of Global Capitalism uses the examples of Cape Breton and Colombia to illustrate the harsh realities suffered by people throughout the global North and the global South under neoliberal globalization, particularly with regard to socio-economic and environmental issues. Ultimately, it exposes the failure of industrial capitalism, and looks toward more sustainable and egalitarian alternatives.